Crisaborole prevents infiltration of neutrophils to suppress itch in a mouse model of atopic dermatitis. Issue 2 (April 2021) - Sakai, Kent; Sanders, Kristen M.; Pavlenko, Darya; Lozada, Taisa; Akiyama, Tasuku
Abstract : The phosphodiesterase-4 inhibitor crisaborole exerts an antipruritic effect and is effective for the treatment of mild-to-moderate atopic dermatitis. However, the mechanisms underlying the antipruritic effect of crisaborole are not completely understood. In this study, we tested whether crisaborole affects spontaneous itch-related behavior as well as neutrophil infiltration and epidermal nerve fiber density (ENFD) in the ovalbumin (OVA)-induced mouse model of atopic dermatitis. OVA treatment resulted in atopic-like skin lesions and spontaneous scratching, which was significantly inhibited by crisaborole treatment. OVA treatment significantly increased neutrophil infiltration and nonpeptidergic ENFD compared with vehicle-treated mice. Crisaborole significantly inhibited neutrophil infiltration without a significant effect on nonpeptidergic ENFD. In a cytokine array, crisaborole significantly decreased neutrophil chemokines, such as CXCL1, CXCL2, and CXCL5. Crisaborole may inhibit atopic dermatitis itch through inhibition of neutrophil infiltration and chemokine expression.